Heat transfer in multi‐phase porous media with application to cancer detection. Issue 1 (15th March 2018) - Niedermeyer, Angela; Heider, Yousef; Stoffel, Marcus; Markert, Bernd
Abstract: Heat transport in biological tissues and its modelling with different approaches, such as Pennes's bioheat equation and porous media theories, is investigated in this study. Breast cancer detection is envisaged as an application. The suitability of the widely‐used Pennes model for breast cancer detection by means of infrared imaging is investigated through experimental and numerical examples. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)